Transthyretin cardiac amyloidosis in continental Western Europe: an insight through the Transthyretin Amyloidosis Outcomes Survey (THAOS) - Damy, Thibaud; Kristen, Arnt V; Suhr, Ole B; Maurer, Mathew S; Planté-Bordeneuve, Violaine; Yu, Ching-Ray; Ong, Moh-Lim; Coelho, Teresa; Rapezzi, Claudio (European heart journal, 2022)
Abstract Aims Transthyretin amyloidosis (ATTR amyloidosis) is a heterogeneous disorder with cardiac, neurologic, and mixed phenotypes. We describe the phenotypic and genotypic profiles of this disease in continental Western Europe as it appears from the Transthyretin Amyloidosis Survey (THAOS). Methods and results THAOS is an ongoing, worldwide, longitudinal, observational survey established to study differences in presentation, diagnosis, and natural history in ATTR amyloidosis subjects. At data cut-off, 1411 symptomatic subjects from nine continental Western European countries were enrolled in THAOS [1286 hereditary (ATTRm) amyloidosis; 125 wild-type ATTR (ATTRwt) amyloidosis]. Genotypes and phenotypes varied notably by country. Four mutations (Val122Ile, Leu111Met, Thr60Ala, and Ile68Leu), and ATTRwt, were associated with a mainly cardiac phenotype showing symmetric left ventricular (LV) hypertrophy, normal diastolic LV dimensions and volume, and mildly depressed LV ejection fraction (LVEF). Morphologic and functional abnormalities on echocardiogram were significantly more severe in subjects with cardiac (n‘= 210), compared with a mixed (n = 298), phenotype: higher median (Q1–Q3) interventricular septal thickness [18 (16–21) vs. 16 (13–20) mm; P = 0.0006]; and more frequent incidence of LVEF <50% (38.1 vs. 17.5%; P = 0.0008). Subjects with cardiac mutations or ATTRwt (or cardiac or mixed phenotype) had a lower survival rate than subjects in other genotype (or the neurologic phenotype) categories (P < 0.0001, for both). Conclusion ATTR amyloidosis genotypes and phenotypes are highly heterogeneous in continental Western Europe. A geographic map of the different disease profiles and awareness that a subset of subjects have a dominant cardiac phenotype, mimicking hypertrophic cardiomyopathy, at presentation can facilitate the clinical recognition of this underdiagnosed disease. Trial registration ClinicalTrials.gov: NCT00628745.